Agricultural Research Plans in Sub-Saharan Africa: A Status Report - Hambly Odame, Helen; Setshwaelo, Louise (International Service for National Agricultural Research, 1997)
In its work serving the national agricultural research systems of sub-Saharan Africa (SSA), ISNAR has found that limited information is available on the current status of national agricultural research plans and related official documentation. In order to identify the stated official priorities for agricultural research and development in SSA, this study reviews the situation of agricultural research planning in 48 SSA countries. Priority setting has become an integral part of research management in agriculture and natural resource management, and this report seeks to fill some of the information gap that exists concerning national priorities for agricultural research and their significance for regional priority setting. This review is presented in three parts: (1) an overview of the state of master planning in SSA as both product and process, (2) an analysis of national Research program priorities and their relation to regional priorities and networking in SSA, and (3) a listing of agricultural research planning documents in SSA.